2015
DOI: 10.1111/iju.12954
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamic findings in women with refractory overactive bladder symptoms

Abstract: Abbreviations & Acronyms BOO = bladder outlet obstruction DO = detrusor overactivity MCC = maximum cystometric capacity MFR = maximum flow rate OAB = overactive bladder PdetQ max = detrusor pressure at maximum flow PFS = pressure flow study Q max = maximum flow SUI = stress urinary incontinence UD = urodynamic UUI = urgency urinary incontinence Objectives: To assess: (i) the correlation between overactive bladder symptoms and urodynamic findings in female patients; and (ii) the association of urinary symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 31 publications
0
23
2
3
Order By: Relevance
“…The authors did not comment on CADO but it was unclear whether an effort was made to identify the entity. 17 The same is true for a study of 537 adults (171 males) with urinary frequency or urinary incontinence who underwent urodynamics evaluation. 18 In another study of 1626 women with mixed urinary incontinence, the authors did not report CADO in any patient.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The authors did not comment on CADO but it was unclear whether an effort was made to identify the entity. 17 The same is true for a study of 537 adults (171 males) with urinary frequency or urinary incontinence who underwent urodynamics evaluation. 18 In another study of 1626 women with mixed urinary incontinence, the authors did not report CADO in any patient.…”
Section: Discussionmentioning
confidence: 93%
“…A study of urodynamics in 1737 women with refractory overactive bladder found positive stress test in 34.3% and detrusor overactivity in 38.7%. The authors did not comment on CADO but it was unclear whether an effort was made to identify the entity . The same is true for a study of 537 adults (171 males) with urinary frequency or urinary incontinence who underwent urodynamics evaluation .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, there are many publications about the positive effects of POP surgery on OAB [ 22 , 23 ]. On the other hand, Zahravi et al still support the general view of International Continence Society (ICS) and they believe that patients with OAB symptoms tend to have a smaller bladder capacity and a higher incidence of detrusor overactivity [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Цей органозберігаючий метод забезпечує високу анатомічну ефективність, нормалізує гемодинаміку, сприяє покращенню якості життя. Водночас використання синтетичних сітчастих матеріалів ускладнює післяопераційний період через часті запалення, відторгнення штучного матеріалу та подальше рецидивування ГП у 8-10% пацієнток, а також спричиняє стресове нетримання сечі після операції [10][11][12][13]. Все це подовжує час, необхідний для лікування пацієнток із ГП; до того ж, згадані матеріали дорого коштують.…”
Section: аналіз літературних даних та постановка завдання дослідженняunclassified